As contribuições do PNAIC-matemática na formação de professores alfabetizadores do município de São Borja - Toja, Ana Paula Uflacker (2018)
This dissertation presents the development of a master's research that aimed to investigate the contributions of the National Pact Program for Literacy in the Right Age (PNAIC) for the continuing education of literacy teachers in the municipality of São Borja / RS, especially the PNAIC-Mathematics which was held in 2014. The research subjects were the literacy teachers of the municipal teaching network of the city of São Borja-RS, who participated in the PNAIC-Mathematics formations and are still acting as a teacher. To base the writing, Laws, Resolutions, the notebooks used in the formations and works of authors like: Imbernón (2010), Garcia (1999), Nóvoa (1992, 2002, 2009), among others, were used. For the data collection, it was decided to apply only one instrument, the questionnaire, which was composed of open and closed questions. The data collected were organized into three final categories, namely: How teachers see continuing education; Contributions of the PNAIC to the Teaching of Mathematics; Difficulties in the teaching of Mathematics for Literacy Teachers. The categories were interpreted through the content analysis of Bardin (2011). According to the data obtained in the research, the actions developed in the framework of the PNAIC influenced the teaching practice in several aspects, which highlight the methodologies that were worked in the formations and that help the teachers in the process of teaching and learning. In addition, the exchange of experience among colleagues was an opportunity to reflect and learn through their own practice and the practice of their colleagues in the profession. It is important to offer the teachers formations, which are appropriate to the daily school life that they are inserted, and that lead them to reflect on their performance in this environment. The formations must be carried out in a continuous way, since to be a teacher is to be in constant process of learning and in search of knowledge. In addition, it is necessary to provide schools with adequate infrastructure for teachers to carry out their work efficiently. Therefore, it is concluded that the PNAIC contributed to the improvement of the teaching practice of literacy teachers, since, after the formations began to use different strategies to work efficiently the mathematical content required in the early years of Elementary School.